A Novel Use of Laryngoscope for Difficult Papanicolaou Smear Collection - Sarah Boudova; Caitlin Thomas; John Wolfe; Jeanne M. Schilder (Case Reports in Obstetrics and Gynecology)
The prevalence of cervical cancer has dropped significantly since introduction of the Papanicolaou (Pap) screen. The greatest risk factor for cervical cancer is inadequate screening. Altered pelvic anatomy can limit the ability to collect a Pap smear. In the presented case, a woman with a history of fibroids and bleeding presented for an exam under anesthesia. Traditional approaches for collecting a Pap smear failed. A GlideScope video laryngoscope was used to visualize the cervix, and a Pap smear was collected. The specimen was satisfactory, negative for intraepithelial lesion or malignancy, and HPV negative. A laryngoscope can be repurposed to visualize collection of a challenging Pap smear. Novel approaches for Pap smear collection and cervical cancer screening are needed and have the potential to save lives.